(untitled) (Archaeologia Adriatica, 2023)
The paper presents the results of an anthropological analysis of a medieval and modern cumulative sample from the area of Dalmatia. The indicators of subadult stress cribra orbitalia and dental enamel hypoplasia (and their mutual correlation) were analysed, as well as their correlation with lifespan and with periostitis as an indicator of non-specific infectious diseases. The results of the work contribute to understanding of the historical living conditions of children at Dalmatia’s archaeological sites, as well as to their comparison with the living conditions of children in continental Croatia and the wider region. The analysis showed slightly better living conditions in Dalmatia compared to continental Croatia, but in both samples the amount of stress to which the children were exposed was extremely high, and the chance of surviving to adulthood was low.